Saccharification of native and degraded cotton cellulose and commercial microcrystalline cellulose by Trichoderma viride cellobiohydrolase I - Finetti, M. (1993)
The degree of polymerization of samples of acid degraded cotton cellulose has no appreciable influence on the saccharification by cellobiohydrolase I from Trichoderma viride. The increase in the number of cellulose molecule ends, achieved by a 30-fold decrease in molecular weight, does not produce the effect which could be expected for a pure end-wise mode of action of this exoglucanase. Microcrystalline celluloses saccharified by the same enzyme yield considerably more reducing sugars than cotton cellulose, either with a similar degree of polymerization or one of about 7000. It appears, therefore, that the difference in the susceptibility of the commercial substrates is not a consequence of their low degree of polymerization.